Sources and Inheritance of Resistance to Brown Planthopper in Some Breeding Lines of Rice - Martinez, C.R.; Khush, Gurdev S. (Wiley, 1974)
The inheritance of resistance to the brown planthopper (Nilaparvata lugens Sial.) in three breeding lines of rice (Oryza sativa L.), IR747B2‐6, IR1154‐243, and IR4‐93, was studied. Seven‐day‐old seedlings were infested with second‐ and third‐instar nymphs of brown planthopper and seedling injury was recorded 7 to 8 days after infestation.The resistance of IR747B2‐6 was conditioned by a single dominant gene which was allelic to the dominant gene of the variety ‘Mudgo’ (Bph 1). The resistance of IR1154‐243 and of IR4‐93 was governed by the same recessive gene which was also allelic to the recessive gene conditioning the resistance of ‘ASD 7’ (bph 2). IR4‐93 inherited its resistance from ‘H‐105.’ But both parents of IR747B2‐6 and of IR1154‐243 were susceptible. We concluded that ‘TKM 6,’ one of the parents of IR747B2‐6, is homozygous for Bph 1 but is also homozygous for a gene, I‐Bph‐1, which inhibits Bph 1. ‘Zenith,’ one of the parents of IR1154‐243, may also have a similar inhibitor gene.